Impact of water stress on the demographic traits and population projection of Colorado potato beetle - Liu, Xia; Yang, Hangxin; Niu, Fushuai; Sun, Hanhan; Li, Chao (Frontiers in Physiology, 2023)
Introduction: The Colorado potato beetle is one of the famous quarantine pests in China which is extremely destructive to Solanaceae crops and causes serious losses to the potato industry. Methods: In this experiment, the host plant potato was subjected to different degrees of water stress to observe the oviposition selection, growth and development, survival, reproduction and population growth of Colorado potato beetles. Results: The results showed that adult Colorado potato beetles laid more eggs on potato plants suitable for water treatment, but fewer eggs on potato plants treated with water stress. The developmental duration of Colorado potato beetles in light drought treatment was shorter than that in control treatment, and the survival rate was higher than that in control treatment. With the aggravation of water stress, the developmental duration was prolonged, survival rate was decreased, and the number of eggs was decreased. Under different water stress levels, the intrinsic rate of increase (r), finite rate of increase (λ), net reproductive rate (R0), and mean generation time (T) of the Colorado potato beetle population were significantly lower than those of control treatment, but there was no significant difference between light drought and control treatment. The TIMING-MS Chart program was used to predict the population dynamics of Colorado potato beetle for 110 days, which showed the fastest population growth in CK treatments and the slowest in HD treatments. The reduced water content of the leaves also reduces the survival rate of adult Colorado potato beetles. The growth, development, survival, and reproduction of Colorado potato beetles are affected by water stress of host plants. Moderate and heavy droughts have negative effects on the development and reproduction of Colorado potato beetles. Discussion: This information can be used to clarify the impact of water stress on the growth, development and population dynamics of Colorado potato beetle, to provide a theoretical basis for the control of this pest.